Moshi Monsters Pick Your Path 1 : Disco Mystery. (London : Sunbird : Ladybird Books, 2011)
There's something strange happening in Monstro City. The Underground Disco has gone eerily silent . . .One of the fangtastic Fizzbangs has gone missing and the other bands are refusing to perform until their friend has returned! Will you see if you can find them, or seek your own monSTARdom in Rockstar Reef? Pick Your Path and decide.
3-6.
Keywords: Moshi Monsters (Virtual reality); Virtual pets -- Fiction